2018
DOI: 10.1029/2017tc004779
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Episodicity in the Early Alpine Tectonic Evolution of the Western Carpathians: How Large‐Scale Processes Are Expressed by the Orogenic Architecture and Rock Record Data

Abstract: The early Alpine tectonic evolution of the Western Carpathian orogenic system is differentiated into four main periods: (i) Middle-Late Triassic rifting and spreading of the Meliata Ocean, but its relationships to the Tethyan realm remain uncertain; (ii) Jurassic subduction of the Meliata oceanic lithosphere and coeval rifting of the Carpathian lower plate and oceanic breakup and spreading of the Atlantic-related Piemont-Váh Ocean, as well as short-term back-arc rifting of the Adriatic upper plate; (iii) Early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 211 publications
(328 reference statements)
2
89
0
2
Order By: Relevance
“…Our age data on the Albian-Early Cenomanian syn-metamor phic wedge D1 stage for ma tion at ap prox i mately 115-95 Ma con tra dicts re con struc tion of the Belice Suc ces sion in the north ern (Infratatric) part of the Považský Inovec Mts., being con tin u ous from the Lower to the Up per Cre ta ceous (Plašienka et al, 1994;Plašienka, 2018). We re port this succes sion was in ter rupted due to the D1 stage tectono-meta morphic event; and this was sug gested in or Putiš and Tomek (2016).…”
Section: Discussion -Constraining the Infratatric Evolutionary Stagesmentioning
confidence: 57%
See 1 more Smart Citation
“…Our age data on the Albian-Early Cenomanian syn-metamor phic wedge D1 stage for ma tion at ap prox i mately 115-95 Ma con tra dicts re con struc tion of the Belice Suc ces sion in the north ern (Infratatric) part of the Považský Inovec Mts., being con tin u ous from the Lower to the Up per Cre ta ceous (Plašienka et al, 1994;Plašienka, 2018). We re port this succes sion was in ter rupted due to the D1 stage tectono-meta morphic event; and this was sug gested in or Putiš and Tomek (2016).…”
Section: Discussion -Constraining the Infratatric Evolutionary Stagesmentioning
confidence: 57%
“…We re port this succes sion was in ter rupted due to the D1 stage tectono-meta morphic event; and this was sug gested in or Putiš and Tomek (2016). Sim i larly, the Váhic sig na tures of ba salt olistoliths in flysch, in ferred by Plašienka et al (1994) or Plašienka (2018), have not been con firmed. Only the Perm ian dom i nant calc-al ka line ba salt and andesito-ba salt olistoliths from a destructured con ti nen tal mar gin as so ci ated with Permian siliciclastics oc cur in the Up per Cre ta ceous flysch (Putiš et al, 2006(Putiš et al, , 2008.…”
Section: Discussion -Constraining the Infratatric Evolutionary Stagesmentioning
confidence: 94%
“…The interpretation of such intrabasinal sources is not unique in the Carpathians. Many continental fragments or ridges have been interpreted in the Western Carpathains (e.g., Czorsztyn and Silesian) with a relatively similar structure (Golonka et al, 2006;Oszczypko, 2006;Plašienka, 2018). The Silesian Ridge was active starting with the Upper Cretaceous and contains gneissic fragments with a peak DZ age of 530-570 Ma and Albian sandstones with a peak DZ age of 600 -630 Ma, as well as distinctive older peaks from 1,250 to 2,740 Ma (Budzyń et al, 2011;Michalík et al, 2006), not found in the internal Carpathian units such as the Dacia Block.…”
Section: 1029/2019tc005780mentioning
confidence: 99%
“…One interesting place to understand the geometry of the subducted ocean and its attached passive continental margin is the Carpathians system of Central Europe (Figure 1a). The Carpathians and their transition into the Balkanides Mountains represent a highly curved orogenic system that formed in response to the opening and closure of an oceanic domain that was kinematically linked to the Alpine Tethys Ocean (e.g., Favre & Stampfli, 1992;Plašienka, 2018;Schmid et al, 2008). Building on numerous previous studies, the Jurassic to Miocene evolution of surrounding continental units has been more precisely and quantitatively reconstructed by accounting for the record of continental breakup, Figure 1b; (b) Tectonic map of the Romanian Carpathians (after Mațenco, 2017 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In the sense of the latest syntheses on the geological structure of the Western Carpathians (Plašienka in Froitzheim et al 2008;Plašienka 2018), the triple regional tectonic zonation is generally accepted. This division includes the Inner Western Carpathians (IWC) in the south, the Central Western Carpathians (CWC) in the middle, and Outer Western Carpathians in the north.…”
Section: Geological Backgroundmentioning
confidence: 99%